No apparent effect of feather heavy metal levels on exploratory behavior of streak-backed orioles (Icterus pustulatus) living near mining waste in central Mexico - Kiere, Lynna Marie; Amaro Flores, Oscar Josue; Maldonado Gómez, Jocelyn Nathaly; García-Hernández, Jaqueline; G-Santoyo, Isaac; Osorio-Beristain, Marcela (Frontiers in Bird Science, 2025)
Heavy metals and metalloids (HM) such as lead, arsenic, cadmium, and mercury are well known to have toxic effects in numerous biological systems. Mining waste is a major source of HM pollution worldwide. Here, we address the effects of HM exposure from living near abandoned mining waste in the Huautla mining district of central Mexico on the exploratory behavior of the streak-backed oriole. Using a field-implemented novel environment test, we quantified individuals’ movements, visual scans, and self-directed behaviors; then, we quantified the concentrations of four toxic (arsenic, lead, mercury, cadmium) and two essential HM (copper, zinc) from their contour feathers. Using principal components analysis to summarize behavioral variables showed that there were three main axes of variation (77% of variance), describing overall activity (32.8%), visual scans versus self-directed behaviors (24.5%), and exploration latency (19.9%). None of these components was affected by any of the HM or interactions among them. This was somewhat surprising, given that we found exceedingly high levels of arsenic and moderate levels of lead, mercury, and copper (though no detectable cadmium or zinc). Further work will be needed to disentangle the relative importance of different HM, temporal mismatch between HM circulating in the body and those measured in feathers, and the possibility of detoxification, adaptation, or selective filters earlier in the life cycle of this population, which has been exposed to mining waste for many generations.